Mrs Kelly - Kieza, Grantlee (Sydney, NSW : HarperCollins Publishers Australia, 2017)
"Ellen Kelly. Wife of a convict. Mother to outlaws. Witness to history ... Mrs Kelly is the astonishing story of one of Australia's most notorious women and her wild family, but it's also the story of the making of Australia, from struggling colony and backwater to modern nation."--Dust jacket.
Includes bibliographical references (pages 529 - 604) and index.
Keywords: Kelly, Ellen; Kelly, Ned, -- 1855-1880 -- Family; Women -- Victoria -- Biography; Matriarchy -- Victoria; Australian